The Use of Storytelling to Develop The Cognitive Aspects of High Order Thinking Skills (HOTS) in Ninth Grade Junior High School - Azzahra, Nuraini; Gaffar, Muhammad Andriana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study investigates how storytelling techniques can help students enhance their cognitive aspects of HOTS. The data for this study were gathered through class observations, teacher and student interviews, and field notes with one participant teacher and thirty-three ninth-grade students. According to the previous research, students can improve their cognitive aspects ability through a variety of methods, one of which is storytelling. Storytelling can help students to hone their ability to analyze, evaluate and create well. However, there are certain students who have yet to master this skill. And the results show that storytelling techniques can increase HOTS cognitive abilities when people are more fully involved in storytelling activities and subsequently have talks about analyzing stories together. The teacher asked them to find stories and tell stories in front of the class. This practice is another solution for how to apply storytelling technique to develop students’ cognitive aspects of HOTS in schools with limited of facilities and infrastructure. Then it was found that they could master the material and analyze and evaluate the problems in the story through this application. Students stated that the storytelling technique made it easier to understand the learning material and seemed exciting.